Hot-wire chemical vapour deposition of silicon carbide thin films from pure silane and methane gases / Fatemeh Shariatmadar Tehrani - Tehrani, Fatemeh Shariatmadar (2013)
A hot-wire chemical vapour deposition (HWCVD) system is a simple and cost-effective technique for deposition of Si-based films. Silicon carbide (SiC) on the other hand is a very interesting material with many unique properties. This work is directed towards understanding how the structural properties of the SiC films affect the opto-electronic properties of the films. This is important for application of this wide band gap semiconductor as a window material in photovoltaic solar cells. In this work, an HWCVD system built in the laboratory is successfully utilized to grow multi-phased SiC films from silane (SiH4) and methane (CH4) gases without hydrogen dilution. In the first part of this work, the influence of precursor gas concentration on chemical bonding, crystallinity and elemental composition of the films is studied. The precursor gas concentration is changed by depositing films at different CH4 flow-rates with the SiH4 flow-rate fixed at SiH4 starving condition and at different total gas partial pressures with the fixed ratio of SiH4 to CH4 flow-rate. In the second part of this work, the effects of deposition pressure and substrate-to-filament distance on the structural and optical properties of films are investigated. The deposition pressure controls the residence time of precursor molecules in the reactor and the filament-to-substrate distance determines the energy of the radicals reaching the growth sites. Then, the structural properties of the films are studied with respect to the optical energy gap (Eg), refractive index (n), and photoluminescence properties of the SiC films. The final part of this work focuses on the growth mechanism of SiC films. In this work, high quality SiC films have been successfully grown in the HWCVD system. The highest growth rate of the SiC films achieved in this work is higher than reported values for films grown by conventional deposition techniques. It is established that the formation of SiC nano-crystals can be manipulated by controlling the CH4 to SiH4 flow-rate ratio in SiH4 starving condition. It is also shown that an optimum total gas partial pressure is required for the formation of SiC nano-crystalline phases in the films. The decrease in filament-to-substrate distance is shown to promote the formation of nano-crystalline SiC phases and hydrogenated amorphous carbon (a-C:H) clusters in the film structure. It is verified that the structure of SiC films grown is independent of the substrate used for the films. Also, It is shown that the Eg and n values are strongly affected by the structural properties of the films such as the Si-C bond density and the presence of a-C:H clusters. Compositional analysis showed that the carbon content controls both the Eg and n values of the films. Photoluminescence emission from the SiC films is the result of band-to-band transition and radiative recombination processes in the band tail states. The precursor gases concentration in the reactor, residence time of the precursor gas molecules, growth radicals in the reactor, and the flux of energetic growth radicals determine the growth mechanism involved in the growth process of the SiC thin films by HWCVD technique.